From Murabbi to Service Provider: The Loss of Adab and Commodification of Teachers in Indonesia’s Elite Islamic Schools - Agung Tri Prasetia; Yan Guspriadi; Habib Hidayatullah (Universitas Negeri Padang, 2025)
This article explores the transformation of teachers in Indonesia's elite Islamic schools from moral exemplars (murabbi) to service providers, set against processes of middle-class social reproduction. Drawing on Pierre Bourdieu's theory of capital conversion and symbolic violence, complemented by Syed Muhammad Naquib al-Attas's concept of the